25th International Conference on Software Engineering, 2003. Proceedings. 2003
DOI: 10.1109/icse.2003.1201204
|View full text |Cite
|
Sign up to set email alerts
|

New directions on agile methods: a comparative analysis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
289
0
24

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(368 citation statements)
references
References 31 publications
2
289
0
24
Order By: Relevance
“…In 2003 Abrahamson et al found 'a jungle of emerged software development methods', and a lack of empirical evidence to support ideas [8]. In 2008, Dingsøyr et al [9], stated that the primary challenge for agile research was to combine academic rigour with industrial relevance, suggesting that researchers could use research methods such as action research as a way to increase relevance and impact.…”
Section: Related Workmentioning
confidence: 99%
“…In 2003 Abrahamson et al found 'a jungle of emerged software development methods', and a lack of empirical evidence to support ideas [8]. In 2008, Dingsøyr et al [9], stated that the primary challenge for agile research was to combine academic rigour with industrial relevance, suggesting that researchers could use research methods such as action research as a way to increase relevance and impact.…”
Section: Related Workmentioning
confidence: 99%
“…Scrum is one of the agile development software development processes [1] where the focal aspects are simplicity and speed [9]. It progresses via a series of iterations called sprints, typically 2 -4 weeks long.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, there are a couple of dissenting texts which describe agile methods, and XP in particular, as irrational and vague (McBreen 2003;Stephens and Rosenberg 2003). In addition, quite a few also highlight the fact that some agile method practices are nonprescriptive, and represent a high level of abstraction, lending themselves to inconsistent interpretation and implementation (Abrahamsson et al 2002;Boehm and Turner 2004;Koch 2005). On the other hand, however, there is at least one proprietary text to accompany every agile method, with an entire series of texts dedicated to XP.…”
Section: Clarity and Rationale Behind Practicesmentioning
confidence: 99%